THE USE OF ARCHIVED GIEMSA-STAINED BLOOD SMEARS AND RDT FOR PCR-BASED GENOTYPING OF Plasmodium vivax MEROZOITE SURFACE PROTEIN-1 IN CENTRAL KALIMANTAN PROVINCE, INDONESIA - Lestarisa, Trilianty; Arwati, Heny; Dachlan, Yoes Prijatna; Keman, Soedjajadi; Safruddin, Din (African Journal of Infectious Diseases (AJID), 2021)
Background: Plasmodium vivax is transmitted most across the country of Indonesia. The country has set out a malaria elimination program by 2030. The information on genetic diversity of malarial parasites relates to malaria transmission in an endemic area may provide the information that can help the malaria control program to achieve the target. Therefore, the purpose of this study was to determine the genetic diversity of the Pvmsp-1 gene in Central Kalimantan Province. Materials and Methods: Samples were 140 of archived Giemsa-stained blood smear and rapid detection test. Samples were divided into the indigenous and migrant populations. After confirmation by single-step PCR, only P. vivax and mixed infection samples were amplified to nested PCR for genotyping of Pvmsp-1 allelic variation in segments F1, F2, and F3. Results: Genotyping of 23 PCR positive samples resulted in 13 genotypes. In segment F1, three allelic variants type A containing subtype A1 (1,050 bp), A2 (350 bp), A3 (150 bp), and type B (100 bp). In segment F2, mono genotypes were detected as variant type A (1,050 bp) and type B3 (150 bp), multiple genotypes were detected as type B containing subtype B1 (250 bp), B2 (200 bp), and B3 (150bp). In segment F3, three allelic variants generated from four mono genotypes were type A (350 bp), type B (300 bp), and two type C (250 bp). Conclusion: The low allelic variation of Pvmsp-1 gene may reflect the actual situation of the low malaria endemic status of the study sites.